2010
DOI: 10.3390/medicina46110104
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pain evaluation for more accurate diagnosis of painful diabetic polyneuropathy

Abstract: Pain is a common problem in diabetic neuropathy, but relatively little has been published regarding the extent to which it needs to be addressed in clinical practice. Objective. To assess neuropathic pain profile and its association with quantitative sensory testing in painful diabetic polyneuropathy. Material and methods. Altogether, 61 consecutive diabetic inpatients with symmetric neuropathic complaints were enrolled. Clinical neurological examination and quantitative sensory testing (QST) were performed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Furthermore, Gierthmühlen et al indicated no correlation for self‐reported thermal pain or self‐reported numbness and the equivalent parameter upon QST. Petrikonis et al only found ‘… a tendency of correlation…’ for the superficial pain items derived from the Neuropathic Pain Scale with QST, but not for deep pain characteristics (Petrikonis et al., 2010). Therefore, it can be assumed that QST‐parameters and self‐reported symptoms accord to some extent, but the results of this study do not allow to generalize that QST and questionnaires assess the same psycho‐somatosensory aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gierthmühlen et al indicated no correlation for self‐reported thermal pain or self‐reported numbness and the equivalent parameter upon QST. Petrikonis et al only found ‘… a tendency of correlation…’ for the superficial pain items derived from the Neuropathic Pain Scale with QST, but not for deep pain characteristics (Petrikonis et al., 2010). Therefore, it can be assumed that QST‐parameters and self‐reported symptoms accord to some extent, but the results of this study do not allow to generalize that QST and questionnaires assess the same psycho‐somatosensory aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Common painful symptoms also include sharp or lancinating pain attacks, allodynia, cramping and gnawing. 10,11 These symptoms are commonly used in rating scales and standard pain questionnaires to assess frequency and severity of painful symptoms, and treatment response. Moreover, since each type of pain is believed to be caused by a different pathophysiological mechanism, therefore, each neuropathic pain medication might have a different effect on sensory symptoms.…”
Section: Pdn Pain Syndromementioning
confidence: 99%
“…Incorporating standard pain questionnaires in clinical evaluation will also aid earlier diagnosis and better management in these patients. 11 In our study, 13 we used the DN4 questionnaire, which has been validated as a reliable screening tool for neuropathic pain in diabetic patients. 14 The questionnaires can be used to screen and differentiate between neuropathic and non-neuropathic pain.…”
Section: Pdn Pain Syndromementioning
confidence: 99%
“…Common pain symptoms are sharp, lancinating, burning, prickling, deep aching, cramping, and gnawing. Upon examination, hyperalgesia and allodynia were frequently found . Therefore, it is the most common cause of neuropathic pain .…”
Section: Introductionmentioning
confidence: 99%
“…Upon examination, hyperalgesia and allodynia were frequently found. 3,4 Therefore, it is the most common cause of neuropathic pain. 5 Patients with PDN have a lower quality of life, especially the physical aspect.…”
Section: Introductionmentioning
confidence: 99%